Analysis of Service Quality in MIPA Laboratory Management Based on Work Culture and Impact on Student Loyalty - Muchsin, Muchsin; Wahyudin, Agus; Yulianto, Arief; Handoyo, Eko (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of MIPA (Natural Sciences and Mathematics) laboratory service quality on work culture and student loyalty in a higher education setting. Employing a quantitative approach with a survey method, the research involved 116 students from Mathematics Education, Chemistry, Biology, and Physics programs at Jabal Ghafur University. The research instruments were tested for validity and reliability using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results reveal that service quality has a positive and significant influence on work culture and a highly significant direct impact on student loyalty. Conversely, work culture exhibits no direct or mediating influence on student loyalty. This underscores that students' perceptions of service quality are the primary factor shaping their institutional loyalty, while work culture plays a more internal organizational role. These findings imply that enhancing laboratory service quality particularly in areas like tangibility, empathy, and reliability should be prioritized in strategies to boost student loyalty. Although work culture remains vital for internal management, it does not serve as a significant intermediary between service quality and student loyalty.